2012
DOI: 10.1088/0031-9155/57/21/6999
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasound on adherent microbubble contrast agents

Abstract: An investigation into the effect of clinical ultrasound exposure on adherent microbubbles is described. A flow phantom was constructed in which targeted microbubbles were attached using biotin-streptavidin linkages. Microbubbles were insonated by broadband imaging pulses (centred at 2.25 MHz) over a range of pressures (peak negative pressure (PNP) = 60-375 kPa). Individual adherent bubbles were observed optically and classified as either being isolated or with a single neighbouring bubble. It is found that bub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…It has been shown that ultrasound pulses with even medium amplitude are able to detach targeted microbubbles (Loughran, et al 2012). Unlike imaging vascular endothelial targets where shear stress from blood flow can detach the microbubbles from their bound sites, reducing ultrasound signal, the flow is very limited outside the vasculature and any detached bubbles could potentially stay in position and continue to contribute to ultrasound signal.…”
Section: Ultrasound Pulses On Detachmentmentioning
confidence: 99%
“…It has been shown that ultrasound pulses with even medium amplitude are able to detach targeted microbubbles (Loughran, et al 2012). Unlike imaging vascular endothelial targets where shear stress from blood flow can detach the microbubbles from their bound sites, reducing ultrasound signal, the flow is very limited outside the vasculature and any detached bubbles could potentially stay in position and continue to contribute to ultrasound signal.…”
Section: Ultrasound Pulses On Detachmentmentioning
confidence: 99%
“…It has also been found that as ARF insonation pressure increases, secondary radiation force can overcome molecular binding forces, and allow bound microbubbles to dislodge or cluster 4850 . Loughran and colleagues determined that the peak negative pressure necessary for secondary radiation forces to overcome the molecular binding forces of adherent microbubbles was approximately 150 kPa 49 . In the imaging sequence employed in this study, PI, B-mode, and ARF transmissions had peak negative pressures of 286 kPa, 115 kPa, and 255 kPa, respectively without accounting for attenuation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, bound microbubbles are subject to secondary Bjerknes forces which may cause detachment of bound microbubbles at low MI (Garbin et al 2011; Gessner et al 2012b; Loughran et al 2012). These forces may induce microbubble unbinding in this method due to lower pressure pulses acting on a microbubble before the dual focus is aligned with the microbubble, potentially reducing sensitivity if detached microbubbles flow out of plane before being detected.…”
Section: Discussionmentioning
confidence: 99%